Production of [xi][star] resonances in [sigma]- induced reactions at 345 GeV/c - Adamovič, M. I.; Siebert, Hans-Wolfgang (Arxiv, 1999)
We report on a measurement of the differential and total cross sections of inclusive production of Xi resonances in Sigma - nucleus collisions at 345 GeV/c.